Chemical composition, antioxidant and insecticidal activities of a new essential oil chemotype of Pinus nigra ssp. mauritanica (Pinaceae), Northern Algeria. (4th March 2022) - Adjaoud, A.; Laouer, H.; Braca, A.; Cioni, P.; Moussi, K.; Berboucha-Rahmani, M.; Abbaci, H.; Falconieri, D.
Abstract: Essential oil (EO) of aerial parts (twigs and needles) of an Algerian-Moroccan endemic pine Pinus nigra Arn. ssp. mauritanica (Mair. & Pey.) (Pinaceae) collected in Northern Algeria were extracted by hydrodistillation (HD) and solid phase micro-extraction (SPME). The compounds were analysed using Gas Chromatography (GC) and GC-Mass Spectrometry (GC-MS). The mean oil yield was 0.23%, for twigs and 0.47% for needles. 83 and 91 compounds have been identified for needles and twigs respectively. Chemical divergences from all other studied Black pines worldwide were observed in needles where the major components identified by HD are β-caryophyllene (26.2%), germacrene D (17.2%), α-pinene (9.4%) unveiling a new chemotype. Significative qualitative and quantitative differences were observed in chemical composition, depending on both technics HD and SPME. Twigs showed a higher potential for the antioxidant activities DPPH, ABTS and β-carotene system than EO needles. In other hand, needles revealed a higher activity for all concentrations than twigs with significant differences (p < 0.05). For phosphomolybden tests, both EOs exhibited more significant antioxidant potential compared to the DPPH, ABTS, β-carotene and reducing power systems. Noticeable insecticidal effects with variable rate depending on used plant parts, concentration, duration and frequency of exposure were also observed.